Synthesis and characterization of titanium and titanium nitride deposition on high speed steel substrate - Kumar M.R.; Behera C.K.; Mohan S.; Aich S. (My University, 2025)
In the present study, titanium and titanium nitride are deposited on the high speed steel at ambient temperature and the tribological behavior is investigated. The deposited high speed steels are characterized by different experimental techniques. scanning-electron microscopy (SEM) is used for film morphology and fractured cross-section examination. However, Profilometer is used for measuring the film thickness and roughness. Nano-indentation is used to extract the intrinsic hardness and youngs modulus evaluation. Ball on-disc sliding test under dry condition at ambient temperature is employed for tribological properties of deposited high speed steels. The test results indicate the improvement in the hardness of titanium nitride deposited high speed steel as compared to other deposition leads to improvement in the tribological properties. The tribological properties have been correlated with the hardness and the morphology of the worn surfaces. © 2019 Elsevier Ltd. All rights reserved.